2013
DOI: 10.1371/journal.pone.0067191
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Regulation of the BST2 (Tetherin) Promoter Enhances Cell Proliferation and Apoptosis Evasion in High Grade Breast Cancer Cells

Abstract: Normal cellular phenotypes that serve an oncogenic function during tumorigenesis are potential candidates for cancer targeting drugs. Within a subset of invasive primary breast carcinoma, we observed relatively abundant expression of Tetherin, a cell surface protein encoded by the Bone Marrow Stromal Cell Antigen (BST2) known to play an inhibitory role in viral release from infected immune cells of the host. Using breast cancer cell lines derived from low and intermediate histopathologic grade invasive primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 32 publications
(38 reference statements)
1
39
1
Order By: Relevance
“…Despite the contradictory effects of BST-2 in various cancers in vitro, Sayeed et. al., showed that elevated BST-2 expression renders high grade breast cancer cells resistant to pro-apoptotic drug (tamoxifen and staurosporine) treatment [123]. These data point to a functional role of BST-2 in breast cancer both in the promotion/progression of breast cancer and its resistance to treatments.…”
Section: Functional Roles Of Bst-2 In Cancermentioning
confidence: 82%
See 2 more Smart Citations
“…Despite the contradictory effects of BST-2 in various cancers in vitro, Sayeed et. al., showed that elevated BST-2 expression renders high grade breast cancer cells resistant to pro-apoptotic drug (tamoxifen and staurosporine) treatment [123]. These data point to a functional role of BST-2 in breast cancer both in the promotion/progression of breast cancer and its resistance to treatments.…”
Section: Functional Roles Of Bst-2 In Cancermentioning
confidence: 82%
“…The spectrum of BST-2 expression in various cancers has been revealed using meta analyses studies of large tumor datasets [119]. In solid tumors, BST-2 expression is elevated in head and neck cancer [120], lung cancer [121], breast cancer [119,122,123], cervical cancer [124], myelomas [125,126], endometrial cancer [127], and glioblastoma [128]. In addition, data from proteinatlas.org reveal that BST-2 is overexpressed in colorectal cancer, ovarian cancer, thyroid cancer, and pancreatic cancer (http://www.proteinatlas.org/ ENSG00000130303-BST2/cancer).…”
Section: Bst-2/tetherin: Roles In Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Cai et al also reported BST-2 protein expression to be associated with breast cancer bone metastasis in a smaller cohort (n=50) of breast samples (22). Experimental data, based on cell lines and in vivo models, have hinted that BST-2 was involved in increased proliferation and reduced apoptosis (23), as well as increased migration, invasion and metastasis (21,22,24). The data we are presenting imply that the role of BST-2 in metastasis is specific to patients with ER-negative tumours, and may be further enhanced by sLe x expression.…”
Section: Discussionmentioning
confidence: 97%
“…Certainly, in our analysis, we found RBPs that were already reported to contribute to the aggressiveness of the high grade cancers. These included IGF2BP3 [34, 54], S100A4 [59, 60], METTL1 [51], NPM1 [61, 62], BST2 [63], and EIF4E2 [64]. We also validated the role of two upregulated and aggressiveness related RBPs (METTL1 and OAS1) in chemoresistance of LN229 glioma cells to temozolomide.…”
Section: Discussionmentioning
confidence: 98%